2017
DOI: 10.3390/nu9121314
|View full text |Cite
|
Sign up to set email alerts
|

Is Trabecular Bone Score Valuable in Bone Microstructure Assessment after Gastric Bypass in Women with Morbid Obesity?

Abstract: Introduction: The effects of bariatric surgery on skeletal health raise many concerns. Trabecular bone score (TBS) is obtained through the analysis of lumbar spine dual X-ray absorptiometry (DXA) images and allows an indirect assessment of skeletal microarchitecture (MA). The aim of our study was to evaluate the changes in bone mineral density (BMD) and alterations in bone microarchitecture assessed by TBS in morbidly obese women undergoing Roux-en-Y gastric bypass (RYGB), over a three-year follow-up. Material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…Schafer et al found that significant bone loss after RYGB occurred in postmenopausal women as early as 6 months postoperatively and persisted through the study duration, which was only 12 months. Using the trabecular bone score as an indirect assessment of skeletal microarchitecture, women had preserved bone microarchitecture for at least 3 years after RYGB . In a smaller study of both genders, bone strength by HR‐pQCT was preserved for a year after bariatric surgery (LAGB, RYGB, or BPD/DS) .…”
Section: Executive Summarymentioning
confidence: 99%
“…Schafer et al found that significant bone loss after RYGB occurred in postmenopausal women as early as 6 months postoperatively and persisted through the study duration, which was only 12 months. Using the trabecular bone score as an indirect assessment of skeletal microarchitecture, women had preserved bone microarchitecture for at least 3 years after RYGB . In a smaller study of both genders, bone strength by HR‐pQCT was preserved for a year after bariatric surgery (LAGB, RYGB, or BPD/DS) .…”
Section: Executive Summarymentioning
confidence: 99%
“…Therefore, TBS seems to be a better measure of bone fragility in individuals who are obese/overweight and useful in assessing osteoporotic fracture risk, with lower TBS values associated with increased fracture risk. Lately, a prospective study on 38 morbidly obese white women, undergoing Roux-en-Y gastric bypass (RYGB) procedure, followed up to 3 years, demonstrated that the fracture risk, calculated by FRAX® algorithm (University of Sheffield, Sheffield, UK), with and without adjustment by TBS, was low, and the authors interestingly concluded that women undergoing RYGB in the mid-term have a preserved bone microarchitecture assessed by TBS (14). However, larger randomised prospective clinical trials will be necessary before suggesting TBS as a significant valuable technique for the prediction of fracture risk in obese subjects.…”
Section: Obesitymentioning
confidence: 99%
“…To date, very few studies have evaluated TBS after bariatric surgery [42,66]. In a previous study reported by us including 38 obese women with an initially normal TBS score, 26.3% of patients had abnormal TBS values 3 years after RYGB [67]. In the present cohort, abnormal TBS at 5 years (partial or totally degraded) reached 85% of patients after mRYGB, but also about 50% of those undergoing restrictive procedures.…”
Section: Discussionmentioning
confidence: 41%